Empowering The Young Generation Through Hadroh Training At The Baitul Muminin Mosque, Gebang Village, Gebang District, Cirebon Regency - Siti Aisyah; Ahmad Khotibul Umam; Ibnu Rusydi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
Hadroh is an Islamic tradition in which historical sentences from the Prophet, prayers and dhikr are chanted by the reader. Hadroh can be attended by all groups and all levels and ages, usually the hadroh itself includes musical instruments in the form of: Darbuka, Bass, Tam, Terbangan/Genjring as well as other supporting musical instruments such as sound systems and mics. Adolescents aged 10-21 years whose emotions are not yet stable, according to several experts, the teenage phase is a transitional phase from childhood to adulthood. The characteristics of adolescence can also be seen from several changes that occur both physically in men and women, as well as changes in mental terms. The aim of this research is so that teenagers do not choose the wrong environment, preventive efforts need to be carried out, with this Hadroh Training is a preventive effort so that teenagers, especially in Gebang Village, Gebang District, Cirebon Regency, can be more productive and make the young generation socially qualified. religion and self-skills. The method used in this research is a qualitative method, namely describing through the results of interview data and from relevant sources. Teenagers from the Baitul Muminin Mosque, Gebang, hold hadroh training which is held once a week, namely on Wednesday evenings in the courtyard of the Bitul Muminin Mosque, Gebang Village, attended by 20 teenagers aged 10-21 years.